Ethylenediamine mediated luminescence enhancement of pollutant derivatized carbon quantum dots for intracellular trinitrotoluene detection: soot to shine. Issue 57 (21st September 2018) - Devi, S.; Gupta, Raju K.; Paul, A. K.; Kumar, Vinay; Sachdev, Abhay; Gopinath, P.; Tyagi, S.
Abstract : Vehicle-generated toxic pollutants are composed of gaseous smoke and particulate byproducts accumulated as a black substance at its exhaust. Abstract : Vehicle-generated toxic pollutants are composed of gaseous smoke and particulate byproducts accumulated as a black substance at its exhaust. This particulate matter (soot) is utilized for the green synthesis of highly stable, non-toxic, environment friendly, carbon quantum dots (CQD). The CQDs are synthesized via the simple hydrothermal route in the absence (C1) and presence (C2) of oxidants. The as-synthesized CQDs are amine functionalized using ethylenediamine. The amine functionalized CQDs (C1N and C2N) are explored for trinitrotoluene detection. From transmission electron microscopy, the average size of C1 and C2 was found to be about 4.2 nm and 5.6 nm respectively. The incorporation of amine groups lead to an increase in quantum yields from 5.63% to 12.7% for C1 and from 3.25% to 8.48% for C2 QDs. A limit of detection (LOD) of 13 ppb was displayed by C1N while the LODs of 11 ppb and 4.97 ppb were delivered by C2N at λ ex 370 nm and λ ex 420 nm respectively. The Stern–Volmer constant for C1N is 2.02 × 10 6 M −1 while for C2N at λ ex 370 nm and λ ex 420 nm is 0.38 × 10 6 M −1 and 0.48 × 10 6 M −1 respectively. Furthermore, C1N presents high selectivity for TNT compared to C2N. Owing to their higher luminescence, C1N particles are successfully demonstrated for their applicability in intracellular TNT detection.